Influence of Construction-Induced Effects and Post-Grouting on the Performance of Mud-Protected Bored Piles: A Numerical Investigation - Hua Mo; Haopeng Liao; Xiangfeng Guo; Mi Zhou (Buildings)
Mud-protected bored piles are widely used in foundation engineering due to their high bearing capacity and strong adaptability to various geological conditions. However, the formation of mud skin around the pile shaft and sediment at the pile bottom during construction significantly affects their mechanical behavior, posing challenges for performance evaluation and design optimization. The post-grouting technique, which involves injecting grout material to strengthen the bottom and surrounding soils, has been practically adopted to enhance pile performance. This study investigates the effect of construction-induced factors (mud skin and sediment) and post-grouting on the performance of mud-protected bored piles. Finite element analyses were conducted based on a super-long test pile (60 m in length, 1.8 m in diameter) from an infrastructure project in Eastern China. The numerical model was validated against field test measurements and previously published numerical results. The results reveal that mud skin and sediment individually decrease the bearing capacity by 28% and 24%, respectively, compared to ideal conditions. When both factors are present, the bearing capacity is decreased by 36%. The post-grouting technique effectively improves pile performance, increasing the bearing capacity by 81% compared to non-grouting conditions. The findings also demonstrate that side friction dominates the bearing behavior of the studied super-long pile, accounting for approximately 90% of the total bearing capacity. Parametric analysis indicates that post-grouting effectiveness varies with soil properties and dimensions of effective grouting zones, showing greater improvement in weak soils. These results provide insights into the mechanisms through which construction-induced effects impact pile performance and offer guidelines for post-grouting applications.